Intra-EEA STRI Database: Methodology and Results - Benz, Sebastian (OECD Trade Policy Papers, 2019)
This paper presents new data on regulatory barriers affecting services trade within the European Economic Area (EEA), covering 25 EEA countries, 22 sectors and five years (2014-2018). Following the methodology of the OECD Services Trade Restrictiveness Index (STRI), qualitative information is scored and weighted to produce binary composite indices. The resulting intra-EEA STRIs reveal that services trade restrictiveness within the Single Market is considerably lower than the applied MFN regime of those EEA members. Moreover, they show that EEA members have achieved significant regulatory harmonisation through their integration process